The animal style in South Russia and China : being the material of a course of lectures delivered in August 1925 at Princeton University under the auspices of the Harvard-Princeton Fine Arts Clubs. - Rostovtzeff, Mikhail Ivanovich. (Roma)
xvi, 112, xxxiii s.